Promoting Sustainable Career Development Through Lifelong Learning: Opportunities and Challenges for the Career Guidance of Young People - Αργυροπούλου Κατερίνα (Education Sciences, 2024)
The sustainability perspective is shaping a new research field in sustainability science by highlighting the positive approach, the development, the evolution, the prosperity and the management of challenge. Sustainable career development suggest the systemic perspective and the dynamic interaction of the individual with the environment in such a way that the individual is self-regulated and evolves. This survey presents the relationship between sustainable career development and developing lifelong learning behaviours in career management of higher education students. The results of the research showed that lifelong learning is a predictor of a sustainable career pattern of young people. The findings are discussed in the context of career guidance and career counseling and a framework for counseling intervention is proposed.